Relationship Between Enteropathogen and Acute Gastroenteritis Disease Severity: A Prospective Cohort Study. (4th October 2017) - Freedman, Stephen; Xie, Jianling; Nettel-Aguirre, Alberto; Lee, Bonita; Chui, Linda; Pang, Xiao-Li; Zhuo, Ran; Parsons, Brendon; Vanderkooi, Otto G; Tarr, Phillip; Ali, Samina; Dickinson, James A; et al.
Abstract: Background: Little is known about the association between specific enteropathogens and disease severity in outpatient children with acute gastroenteritis. Recent advances in diagnostics enabling the rapid and simultaneous detection of common enteropathogens have become readily available. While such knowledge can be used to optimize therapy it also has the potential to predict disease severity. Such knowledge can aid clinical decision making, can clarify guidance and expectations provided to families, and can guide public health policy. Methods: We conducted a prospective cohort study of children with acute gastroenteritis who were brought for emergency department care. The primary outcome measure was the 20-point Modified Vesikari Scale (MVS) score calculated from symptom onset until day14 of follow-up (total MVS score). Stool and/or rectal swab specimens were collected and analyzed for 18 unique pathogens by molecular diagnostic assays (in-house 5 virus panel, Luminex xTAG Gastrointestinal Pathogen Panel) and/or bacterial culture. An enteropathogen was deemed to be present if a candidate pathogen was identified in the rectal swab or stool specimens by any testing method. Binary logistic regression was performed to assess the association between pathogens (including all pathogens as present or not) and disease severity with the dependent variable being the total MVS score categorized as severe (11–20 points) vs.. non-severe (0–10 points). Results: The mean total MVS score (SD) was 12.8 (3.2) and 73.0% (807/1102) of participants experienced severe disease. A pathogen was identified in 72.8% (802/1102) of study participants. Rotavirus, norovirus GII and adenovirus were identified in 26.6% (293/1102), 23.0% (253/1102) and 16.0% (176/1102) of participants respectively. After adjusting for other pathogens significant predictors of severe disease were: rotavirus (OR=8.0; 95% CI: 4.8, 13.2), Salmonella (OR=5.4; 95% CI: 1.2, 24.4), adenovirus (OR=2.1; 95% CI: 1.3, 3.3), and norovirus GII (OR=1.8; 95% CI: 1.3, 2.6). Clostridium difficile (OR=1.6; 95% CI: 0.96, 2.6) and Aeromonas (OR=0.97; 95% CI: 0.2, 4.7) were not significantly associated with severe disease. Conclusion: In children with acute gastroenteritis, the enteropathogens associated with severe disease included rotavirus, Salmonella, adenovirus and norovirus GII. Disclosures: All authors: No reported disclosures.